Effect of the rotational speeds of the screw conveyor and milling roller on the behaviour of grain flows in the connected chamber of a vertical "conveying-milling" rice mill. (December 2022) - Li, Anqi; Jia, Fuguo; Han, Yanlong; Chen, Peiyu; Zhang, Jincheng; Wang, Yinglong; Fei, Jiaming; Shen, Shaohang; Hao, Xianzhi; Feng, Wenyu
Abstract : The continuous feeding rice into a rice mill is one of the main factors affecting milling quality. Understanding the conveying mechanism of rice in the connected chamber is the key to control the feeding, however the internal mechanisms involved remain poorly understood. In this work, the discrete element method was used to simulate rice movement in a rice mill and the validity of the simulation verified by experiments. The influence of rotational speed ratio i on rice conveying effect in connected chamber was analysed. A mathematical model involving the relationship between mill parameters and conveying uniformity was established. The simulations showed that particle groups will enter continuous limited state when particles enter the entrance of milling chamber. In particular, when i was 0.5 and 0.75, the flux near the shaft is even <0. With the increase of i, the rice conveying efficiency increased, but the milling time decreased. When i was <1.25, the amount fed into the milling chamber gradually increased but then suddenly decreased when i was >1.25. The ability of the particle group breaking through the restriction of convex rib increased with i . Thus, the phenomenon of uneven conveying can occur in the conveying process and the mechanism involved is convection. The degree of axial mixing is closely related to the sweep volume difference between screw conveyor and convex rib. This study helped clarify the rice conveying mechanism and provided guidance for the design of rice mills and similar equipment. Graphical abstract: Image 1 Highlights: Rice will enter a continuous limited state when they enter milling chamber entrance. Conveying efficiency increases but milling time decreases with the increase of i. The axial movement of rice particles is mainly inhibited by convex ribs. Rice axial mixing is decided by swept volume difference between screw and rib.